1997
DOI: 10.1538/expanim.46.31
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Proviruses and Viral RNA in the Early Stages of Feline Immunodeficiency Virus Infection in Cats: A Possible Model of the Early Stage of HIV Infection.

Abstract: Feline immunodeficiency virus (FIV) infection in cats has been reported to be a useful animal model for human AIDS studies, especially in the early stages of infection. We examined the temporal changes in provirus detection in peripheral blood mononuclear cells (PBMC) and the distribution of FIV-DNA and RNA in feline tissues by the polymerase chain reaction at 10, 35, 70 days after intravenous inoculation of FIV. Viral DNA in the PBMC was detected three to four weeks after infection and its fluctuation was dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…However, false positives are not uncommon in serological tests (Tozon et al, 2008). Thus, we also found that one cat was only positive through the nested PCR: this animal was possibly at an early stage of infection (when the proviral DNA can be detected in the peripheral blood before antibodies can) (Ohkura et al, 1997). Among the FeLV-positive animals, we found three cats that were negative for p27 and positive through nested PCR, which suggests that regressive/latent infections were present in these animals.…”
Section: Discussionmentioning
confidence: 57%
“…However, false positives are not uncommon in serological tests (Tozon et al, 2008). Thus, we also found that one cat was only positive through the nested PCR: this animal was possibly at an early stage of infection (when the proviral DNA can be detected in the peripheral blood before antibodies can) (Ohkura et al, 1997). Among the FeLV-positive animals, we found three cats that were negative for p27 and positive through nested PCR, which suggests that regressive/latent infections were present in these animals.…”
Section: Discussionmentioning
confidence: 57%
“…Fluctuation in proviral loads during the course of infection due to a decrease in infected CD4+ T cells was reported by others who determined that CD4+ T cell depletion occurred as a result of targeting by cytolytic T lymphocytes and apoptosis (Ohkura et al, 1997). …”
Section: Resultsmentioning
confidence: 70%
“…Dean and Pedersen reported that the thymus carries the heaviest viral burden in the acute phase of infection and that there was an increase in type 2 cytokines which may contribute to the observed inflammation (7). While viral DNA was disseminated throughout most lymphoid tissues at 70 days p.i., viral RNA was produced almost exclusively in the thymus during the acute phase of infection (18). We have demonstrated heavy viral burden in the thymic tissues of FIV-infected young cats monitored for over 1 year (11), suggesting a strong correlation between virus infection of the thymus and subsequent pathologic change.…”
Section: Discussionmentioning
confidence: 72%